Pengaruh Debt Default, Disclosure, Financial Distress, Audit Delay dan Rasio Pasar terhadap Opini Audit Going Concern (Studi pada Perusahaan Sektor Perdagangan Retail yang Terdaftar di BEI tahun 2020-2022) - Hilwa Faradisa, Sindi; Novius, Andri (Basecamp Economics PubMed, 2024)
The purpose of this study was to present, test and analyze the effect of variable Debt Default, Disclosure, Financial Distress, Audit Delay and Market Ratio on Going Concern Audit Opinions in Retail Trading Sector Companies Listed on the Indonesia Stock Exchange in 2020-2022. This research is a quantitative research. The population in this research was 30 Retail Trading Companies in 2020-2022. In this research, the sample selection used purposive sampling, the number of samples used in this research was 25 samples of retail trading companies in 2020-2022. The data analysis methods used are descriptive statistical analysis and logistic regression analysis. Hypothesis testing in this research uses the help of the SPSS version 29 program. Based on the results of the testing research, it was found that the Debt Default, Financial Distress, Audit Delay variables had a significant effect on the Going Concern Audit Opinion. Meanwhile, the Disclosure and Market Ratio variables do not have a significant effect on the Going Concern Audit Opinion.